Empirical Quality Control Analysis on Manufacture Industry Process: A Case Study in Development Country - Armin Darmawan; Syamsul Bahri; Alamsyah Alamsyah (Jurnal Penelitian Enjiniring, 2018)
This article presents an empirical study on quality control in a manufacture industry to determine level of quality control. Case study conducted in a manufacture that produce many concrete products with different specification and size. Paving block product is the main focus on this study. The industry faces problem related the defective product that influence to low performance and high production cost. Therefore, it is crucial to address the main problem and map the level of quality process using Six Sigma approach. Six Sigma is one the most used structure and systematic tool in defining problem, determine the key factors, map the level quality process, and improvement opportunities. The results show that most defect is dominated by Cracks with the percentage of 94,43 % , fracture with 3,91 % and Broken with 1,67 % which will be classified as Critical To Quality (CTQ). Sigma level that obtained from the production process is 4,23 with the level of defective to 3.198 units per million opportunities (DPMO).